The effects of low dose N-acetylcysteine (NAC) as an adjunct to cardioplegia in coronary artery bypass surgery - Koeksal, Hakan; Rahman, Ali; Burma, Oktay; Helifeoglu, Ihsan; Bayar, Mustafa Kemal (Turkish Soc Cardiology, 2008)
Objective: We aimed to evaluate the efficacy of low dose N-acetylcysteine (NAC) against myocardial ischemia-reperfusion damage in coronary artery bypass surgery accompanied by cardiopulmonary bypass (CPB). Methods: Thirty patients operated due to triple coronary artery disease were enrolled into this prospective randomized study (control group - n=15 and NAC group - n=15). N-acetylcysteine was added to induction cardioplegia solution in dose of 4 mmol/l and in dose of 2 mmol/l to maintenance cardioplegia solution in the NAC group. Hemodynamic measurements were performed before and after anesthesia with different intervals. Creatine kinase-MB (CK-MB) levels were analyzed during 24 hours postoperatively. Blood samples were obtained from coronary sinus before CPB (T-1), just before the cross-clamp removed (T-2) and 30 minutes later (T-3). Malondialdehyde (MDA), glutathione peroxidase (GSH-Px), nitric oxide (NO) levels and neutrophil percentage were determined. Statistical analysis was performed using student's t test, Chi-square and two-way ANOVA tests. Results: There were no significant differences between the two groups with regard to the hemodynamic parameters, and CK-MB levels. The MDA levels were significantly lower in NAC group than in control group during reperfusion period (0.75 nmol/l vs 0.88 nmol/l, p < 0.05). Neutrophil percentage in coronary sinus blood was significantly lower in NAC group than in control group during the reperfusion period (77.6% vs 82.7%, p < 0.05). The GSH-Px and NO levels were also not statistically different between groups. Conclusion: Low dose NAC as an adjunct to cardioplegic solutions effectively reduces myocardial oxidative stress in coronary bypass surgery with cardiopulmonary bypass, but may not restore the myocardial injury. (Anadolu Kardiyol Derg 2008; 8: 437-43)
Keywords: N-acetylcysteine; coronary artery bypass surgery; ischemia-reperfusion; cardioplegia